2022
DOI: 10.1111/opo.12982
|View full text |Cite
|
Sign up to set email alerts
|

Trends in low vision service utilisation: A retrospective study based on general population healthcare claims

Abstract: To identify parameters associated with the downward trend in the uptake of Low Vision Services (LVS) in the Netherlands. Methods: A retrospective cohort study was conducted based on a Dutch national health insurance claims database (Vektis CV) of all adults (≥18 years) who received LVS from 2015 until 2018. Descriptive statistics were used to assess socio-demographic, clinical and contextual characteristics and other healthcare utilisation of the study population. General estimating equations trends in charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…Our results also revealed that treatment with intravitreal injections and having cataract surgery lowered the odds of receiving multidisciplinary low vision services, which is in line with our previous qualitative study in which we found that patients with wet macular degeneration treated with intravitreal injections often refuse multidisciplinary low vision service referral because of wanting to await the treatment effect 6 . Furthermore, it has been suggested that treatment with intravitreal injections and cataract surgery might lower multidisciplinary low vision service needs in patients due to a positive treatment effect 13 . Higher costs for ophthalmic encounters lowered the odds for multidisciplinary low vision service uptake, which might be explained by ongoing treatment of patients including diagnostic scans and thus more contact between patients and their ophthalmologists.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Our results also revealed that treatment with intravitreal injections and having cataract surgery lowered the odds of receiving multidisciplinary low vision services, which is in line with our previous qualitative study in which we found that patients with wet macular degeneration treated with intravitreal injections often refuse multidisciplinary low vision service referral because of wanting to await the treatment effect 6 . Furthermore, it has been suggested that treatment with intravitreal injections and cataract surgery might lower multidisciplinary low vision service needs in patients due to a positive treatment effect 13 . Higher costs for ophthalmic encounters lowered the odds for multidisciplinary low vision service uptake, which might be explained by ongoing treatment of patients including diagnostic scans and thus more contact between patients and their ophthalmologists.…”
Section: Discussionsupporting
confidence: 88%
“…To predict receiving multidisciplinary low vision services as the dependent variable, we used multivariable logistic regression models with sociodemographic, clinical, and contextual characteristics and other health care utilization as potential predictors. The selection of predictors was based on the literature, clinical expertise from the authors, and insights gained from our previous studies 6–9,13 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, from an international perspective, different institutions recommend referral to LVS in their clinical practice guidelines for ophthalmologists and optometrists, such as the American Optometric Association (United States) [ 14 ], the Royal College of Ophthalmologists (United Kingdom) [ 15 ], the Low Vision Academy (Italy) [ 16 ] and the Dutch Society of Ophthalmologists (Netherlands) [ 17 ]. Despite these efforts and supporting literature on the benefits of LVS, international studies report underutilization of and lack of access to LVS [ 18 21 ]. There seems to be a mismatch between the potential need and the actual uptake of these services.…”
Section: Introductionmentioning
confidence: 99%